1997
DOI: 10.1177/030913339702100103
|View full text |Cite
|
Sign up to set email alerts
|

Climatic variability and change over southern Africa: a reflection on underlying processes

Abstract: Quasi-periodicities in annual rainfall totals over southern Africa have been identified; in particular, an approximately 18-year cycle may be related to interdecadal variability in sea-surface temperatures in the eastern equatorial Pacific and central Indian Oceans. A 10-year cycle along the south coast is related to variability in standing wave 3. Atmospheric anomalies associated with wet and dry years can be related to changes in the frequency, intensity and persistence of important rainfall-producing weathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
201
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(212 citation statements)
references
References 138 publications
9
201
2
Order By: Relevance
“…It has been observed in regional streamflow (Abbott and Dyer, 1976;Partridge, 1985;Alexander, 1995), as well as in the temperature record (Keen, 1971) and in tree-ring data (Visagie, 1985;Tyson, 1986). Multi-decadal variability in the 16-20-year band has also been observed in ocean temperatures around South Africa (Mason, 1990;Mason and Jury, 1997) and appears to be similar to ∼21-year variability reported in Southern Hemisphere sea surface temperatures (Folland et al, 1984). It is present in historical joint Northern Hemisphere surface air temperature and sea-level pressure (Mann and Park, 1996) and in joint empirical orthogonal function analysis of global historical sea surface temperatures and mean sea-level pressures (Allan, 2000).…”
Section: Variability Over the Period Of Meteorological Recordsupporting
confidence: 59%
“…It has been observed in regional streamflow (Abbott and Dyer, 1976;Partridge, 1985;Alexander, 1995), as well as in the temperature record (Keen, 1971) and in tree-ring data (Visagie, 1985;Tyson, 1986). Multi-decadal variability in the 16-20-year band has also been observed in ocean temperatures around South Africa (Mason, 1990;Mason and Jury, 1997) and appears to be similar to ∼21-year variability reported in Southern Hemisphere sea surface temperatures (Folland et al, 1984). It is present in historical joint Northern Hemisphere surface air temperature and sea-level pressure (Mann and Park, 1996) and in joint empirical orthogonal function analysis of global historical sea surface temperatures and mean sea-level pressures (Allan, 2000).…”
Section: Variability Over the Period Of Meteorological Recordsupporting
confidence: 59%
“…Saji and Yamagata (2003) have used partial correlation analysis to show that the positive IODZM events, rather than El Niño, dominate the enhancement of east African rainfall. At the same time, other studies (Mason and Jury, 1997;Jury et al, 2002;Fauchereau et al, 2003) concluded that east Africa shares a maritime rainfall regime with the west IO, while convection over southern Africa is inversely related. This observation links the southern African rainfall regime to the IODZM.…”
Section: Introductionmentioning
confidence: 86%
“…Tyson et al, 1975;Taljaard, 1986;Walker, 1990;Lindesay and Jury, 1991;Matarira and Jury, 1992;Levey and Jury, 1996;Mason and Jury, 1997;Landman and Mason, 1999;Reason and Mulenga, 1999;Cook et al, 2004). Since many countries in the region have a large rural population and tend to rely on rain-fed agriculture, southern Africa is vulnerable to the impacts of rainfall variability, posing challenges for food security and planning (Vogel and O'Brien, 2003).…”
Section: Introductionmentioning
confidence: 99%